Uncalibrated eye-to-hand visual servoing using inverse fuzzy models - Gonçalves, P.J.S. (2017)
(c) 2007 IEEE. Personal use of this material is permitted. Permission from IEEE must be obtained for all other users, including reprinting/ republishing this material for advertising or promotional purposes, creating new collective works for resale or redistribution to servers or lists, or reuse of any copyrighted components of this work in other works.